Manhaj Dakwah Sheikh Haji Muhammad Waly Al-Khalidy in Aceh:: A Study on the Preservation of the Tawheed - Gunandar, Jerri; Najihah, Najihah (Teunuleh Publisher, 2024)
This article explores the da'wah methodology of Shaykh Haji Muhammad Waly Al-Khalidy, a significant clerical figure in Aceh known for his efforts in preserving the creed of tawhid and advancing da'wah in the region. The study focuses on his community engagement, particularly within Islamic boarding schools and through public lectures (syarahan). It aims to evaluate the impact of his da'wah from historical and contemporary perspectives. The research employs two primary methodologies: library research and field research. The library research involves reviewing previous studies and analyzing various texts related to da'wah and tawhid preservation. Key references include works by Prof. Dr. Muhibuddin Waly, titled